Willem Kolff: father of dialysis - Tejena, Nayeli; Loor, Justhyn; Campos, Nathalia; Mendoza, Gina; Vera, Odalis; Cabrerizo, Claudia T. (Revista Gregoriana de Ciencias de la Salud, 2025)
Dialysis is a vital treatment for patients with chronic kidney failure, enabling the removal of metabolic waste and excess fluids when the kidneys cease to function. Although the idea of blood purification dates back to ancient times, Willem Kolff revolutionized the field by developing the first artificial kidney in 1943, earning the title "Father of Dialysis". This essay examines the historical evolution of dialysis, highlighting the challenges Kolff faced and his medical legacy. Before his innovation, chronic kidney failure was almost invariably fatal due to the lack of effective treatments. Earlier researchers such as Nollet, Dutrochet, and Graham laid the scientific foundation by studying osmosis and diffusion, essential dialysis principles. During World War II, Kolff built the first artificial kidney using rudimentary materials, successfully saving a patient’s life in 1945. Later, he refined this technology in the United States and contributed to developing advanced medical devices. Kolff's invention transformed kidney failure from a fatal condition to a manageable disease, although economic and infrastructural barriers still hinder global access. His legacy inspires modern medicine, emphasizing the importance of innovation in healthcare.